Strategi Guru Agama dalam Menerapkan Proyek Penguatan Profil Pelajar Pancasila Dengan Tema “Bulliying” pada Siswa di SMAN 1 Kota Bengkulu - Febrianto, Redo (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
School is a place to get general education and religious education at elementary and secondary levels. Therefore, this thesis aims to determine the Strategy of Religious Teachers in Implementing the Pancasila Student Profile Strengthening Project with the Theme of "Bulliying" for Students at SMAN 1 Bengkulu City. This type of research uses descriptive qualitative research. The subjects of the study were the P5 coordinator and Islamic religious teachers. Data collection techniques were by means of observation, interviews and documentation. Data validity techniques used triangulation. Data analysis techniques were by means of data reduction, data presentation, and conclusions. The results of the study showed that the Strategy of Religious Teachers in Implementing the Pancasila Student Profile Strengthening Project with the Theme of "Bulliying" for Students at SMAN 1 Bengkulu City was through 4 stages, namely. First, Carrying out the bullying introduction stage. Second, Carrying out the contextual stage by providing examples and impacts of bullying. Third, Real action, by making anti-bullying posters and holding an exhibition to present the results of the posters made by students. Fourth, reflection or follow-up, with students making a commitment not to carry out bullying anywhere and anytime. Supporting and Inhibiting Factors of Religious Teachers' Strategy in Implementing the Pancasila Student Profile Strengthening Project with the Theme "Bulliying" for Students at SMAN 1 Bengkulu City, namely, Supporting Factors: a) Full support from the School and Teachers. b) Cooperation between Parents and Teachers. c) Support from the Guidance and Counseling team that provides understanding materials to students. Then Inhibiting Factors: a) lack of maximum time in implementing activities. b) Demands of a Dense Curriculum. c) Level of Student Acceptance and Understanding.